CONCORRENZA FRA NORME INTERNAZIONALI: IL REGIME GIURIDICO DELL'ANTARTIDE NEL CONTESTO GLOBALE - VIGNI, PATRIZIA (GIUFFRE' EDITORE, 2005)
The existence of several treaty regimes that regulate similar subjects-matters makes difficult to determine which the most appropriate norm is to deal with a specific issue. This book is aimed at identifying different legal theories relating to the overlap of international treaties and formulating an effective solution that allows important issues to be regulated by the most appropriate international provisions. This matter of general concern is specifically analysed with respect to the Antarctic Treaty system